Palliative care, hospice, and advance care planning: Views of people living with HIV and other chronic conditions - Slomka, Jacquelyn (J Assoc Nurses AIDS Care, 2016)
People living with HIV (PLWH) who survive to older adulthood risk developing multiple chronic medical conditions. Health policymakers recognize the role of early palliative care and advance care planning in improving health quality for at-risk populations, but misperceptions about palliative care, hospice, and advance care planning are common. Before testing a program of early palliative care for PLWH and other chronic conditions, we conducted focus groups to elicit perceptions of palliative care, hospice, and advance care planning in our target population. Overall, participants were unfamiliar with the term palliative care, confused concepts of palliative care and hospice, and/or associated hospice care with dying. Participants misunderstood advance care planning, but valued communication about health care preferences. Accepting palliative care was contingent on distinguishing it from hospice and historical memories of HIV and dying. Provision of high-quality, comprehensive care will require changing public perceptions and individuals’ views in this high-risk population.